Consistent kinematic architecture in the damage zones of intraplate strike-slip fault systems in North Victoria Land, Antarctica and implications for fault zone evolution RID C-1391-2009 - Storti F; Laufer AL; ROSSETTI, FEDERICO; SALVINI, Francesco (Journal of Structural Geology, 2006)
Cumulative, polymodal normal (Gaussian distribution) statistics was applied to subsidiary fault data collected from damage zones associated with the Cenozoic Lanterman and Priestley intraplate right-lateral strike-slip fault systems in North Victoria Land, Antarctica. Results show that five Gaussian peaks out of seven in the Lanterman Fault and five out of nine in the Priestley Fault have almost coincident azimuthal values. We named these Gaussian peak pairs as consistent fault sets, arranged in a consistent kinematic architecture that is compatible with the Cenozoic regional strike-slip environment. Angular and kinematic relationships among subsidiary fault sets within the consistent kinematic architecture provide constraints for the inference of the state of stress along the Lanterman and Priestley fault systems. We interpret the fault pattern of the consistent kinematic architecture to be produced by early localisation of the principal displacement zone along pre-existing mechanical discontinuities inherited from the Early Paleozoic Ross Orogeny. Shear localisation was followed by subsidiary faulting at an angle to the principal displacement zone according to the Mohr–Coulomb–Byerlee failure criterion.